Signal Processing, Image Processing and Pattern Recognition International Conference, SIP 2011, Held as Part of the Future Generation Information Technology Conference FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - Kim, Tai-hoon.; Adeli, Hojjat; Ramos, Carlos; Kang, Byeong-Ho.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book comprises selected papers of the International Conference on Signal Processing, Image Processing and Pattern Recognition, SIP 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, in Conjunction with GDC 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of signal processing, image processing and pattern recognition.
Electronic reproduction.
Keywords: Signalprocessing -- Digitaltechniques -- Congresses; Image processing -- Digitaltechniques -- Congresses; Pattern recognition systems -- Congresses; Electronic books